Аксиологический релятивизм понятий «норма» и «отклонение» и его проявление в литературе переходных эпох - Иоскевич, Ольга Александровна (SlavVaria, 2022)
Axiological relativism of the concepts "norm" and "deviation" and its manifestation in the literature of transitional periods. The article discusses the concepts of norm and deviation, and also reveals the specifics of their con- tent. It is emphasized that these concepts are relative and they are determined by a number of socio-cultural and historical factors. The axiological relativism of the concepts of norm and deviation is most clearly manifested in transitional eras in the history of mankind, when there is a change in cultural paradigms and the processes of mastering new spheres of human existence, new knowledge about the world and man are activated. In turn, the intensity of comprehension of these concepts in literature provokes the search for new genre and style solutions and narrative strategies for the implementation of norms and deviations in a work of art.